The psychologically literate citizen foundations and global perspectives - Cranney, Jacquelyn; Dunn, Dana. (New York ; Oxford : Oxford University Press, 2011)
The concepts of psychological literacy and the psychologically literate citizen promise to invigorate a new global approach to psychology education. They pose a basic question: What attributes and capabilities should undergraduate psychology majors acquire?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychology -- Study and teaching (Higher); Psychology